2017
DOI: 10.1590/s1980-6574201700030013
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate mouth rinse reduces rating of perceived exertion but does not affect performance and energy systems contribution during a high-intensity exercise

Abstract: -Aim:The study aimed to verify the effect of carbohydrate (CHO) mouth rinse on time to exhaustion, energy systems contribution and rating of perceived exertion (RPE) during a high-intensity exercise. Methods: Fourteen men performed an incremental exercise test to determine their maximal oxygen uptake and peak power output (PPO) and two time-to-exhaustion tests at 110% of PPO. Participants rinsed their mouth with 25ml of 6.4% of CHO or placebo (PLA) solution immediately before the time-to-exhaustion test, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Mouth rinsing with a CHO solution also did not affect bench press one-rep max, upper-limb muscle endurance, or other anaerobic metabolic capacities [ 12 ]. For this reason, some scholars have noted that mouth rinsing with a CHO solution does not contribute to the energy supply of the metabolic system required during high-intensity exercise [ 21 ]. Unlike other studies, this study explored exercise capacity during inertial resistance exercise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mouth rinsing with a CHO solution also did not affect bench press one-rep max, upper-limb muscle endurance, or other anaerobic metabolic capacities [ 12 ]. For this reason, some scholars have noted that mouth rinsing with a CHO solution does not contribute to the energy supply of the metabolic system required during high-intensity exercise [ 21 ]. Unlike other studies, this study explored exercise capacity during inertial resistance exercise.…”
Section: Discussionmentioning
confidence: 99%
“…First, chemoreceptors from the tongue and oral cavity are stimulated by the CHO solution in the oral cavity, carry a message to the nucleus of the solitary tract, and act on the ventral posterior thalamus of taste, which transmits neurons in the insula cortex and excites the motor cortex. Second, CHO in the human oral cavity produces central neural responses, including the activation of the insula, frontalis, orbitofrontal cortex, and striatum, which comprise the reward and motor control areas of the brain, and thus improves motor performance [21]. Third, Krings et al (2017) observed that gargling with a CHO solution before short-term, high-intensity bicycle sprints significantly decreased the fatigue index [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation